Global capitalism : its fall and rise in the twentieth century - Frieden, Jeffry A. (New York London : W.W. Norton & Company W.W. Norton & Company, 2007)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: 20e eeuw; kapitalisme; globalisering